PHOSPHATE ROCK APPLICATION ON ALFALFA (Medicago sativa L.) PRODUCTION AND MACRONUTRIENTS IN LATOSOL SOIL - Liani, Y.; Hong-Qing, Hu; Sumarsono, S.; Widjajanto, D.W.; Guanjie, Jiang (Diponegoro University, 2011)
The objective of this study was to evaluate the effectiveness of phosphate rocks (PRs) fertilizercompared to chemical P fertilizer for the best crop production and macronutrients of alfalfa. Acompletely randomized design under 3x3 factorial patterns was used in this research. The first factorwas different sources of P fertilizer: Guizhou Phosphate Rock (GPR), Jingxiang Phosphate Rock (JPR),and Single Super Phosphate (SSP). The second factor was level of P fertilizer: 75, 100, and 125 mgP2O5/kg soil. A control treatment (without addition of P fertilizer, CK) was added as a comparison withthe treatments. The results showed that JPR was the best for alfalfa production, whereas GPR and SSPwere better for nutrient content in the alfalfa tissue than JPR. On the whole, phosphate rocks had similareffect on alfalfa growth compared to SSP at the experimental conditions.